A conceptual model to minimise operational cost for free shuttle buses: a case study in Macau. (2016) - Qiao, Sen; Tao, Xiangnan; Ma, Rufei; Xu, Xin-long; Chen, Hsing Hung
To facilitate more convenient travel as the economy of Macau expands, the government of Macau has allowed casinos to add free shuttle buses (FSB) and drivers. In this paper, we optimise the operation cost of FSB based on the number of FSB and FSB's driver population in Macau. Firstly, we investigate the operational conditions of the FSB in each depot, including the transit time of FSB and the number of passengers. Then, we propose a series of integer programming models to optimise the population of FSB and FSB drivers. Finally, through a practical demonstration using Excel to solve the linear programming (LP) model, this paper concludes that the numbers of FSB and drivers have a reduction of 43.68% and 33.6%, respectively. It implies that the operation cost of FSB could be reduced by 270, 900, 000 HKD in purchasing of FSB and 38, 678, 400 HKD/year in employing drivers of FSB.